Hubungan Antara Kadar HbA1c dengan Kadar Trigliserida terhadap Pasien Prolanis Diabetes Melitus Tipe 2 di Laboratorium Klinik Kimia Farma Depok - Putri, Riantika Lutfiana; Aryani, Desi; Safari, Wulan Fitriani (Poltekkes Kemenkes Semarang, 2024)
Diabetes Mellitus (DM) is a group of metabolic disorders characterized by elevated blood glucose levels resulting from abnormalities in insulin secretion, insulin action, or both. Patients with Type 2 DM are at a higher risk of developing cardiovascular diseases, often indicated by dyslipidemia, which is characterized by elevated triglyceride levels, increased Low-Density Lipoprotein (LDL) levels, and decreased High-Density Lipoprotein (HDL) levels. This study employs an analytical observational design. The data obtained shows that controlled and uncontrolled HbA1c levels with normal triglyceride levels were found in 24.7% of the patients, while 75.3% had high triglyceride levels. The data were further analyzed using the Statistical Package for the Social Sciences 25 (SPSS 25) with a non-parametric test, specifically the Chi-Square continuity correction test, with a significance level of p < 0.05. The Chi-Square test results indicated that H0 was rejected and Ha was accepted, with a p-value of < 0.036 for the relationship between HbA1c and triglycerides. These results suggest a correlation between HbA1c levels and triglyceride levels in Prolanis Type 2 DM patients at Kimia Farma Clinical Laboratory in Depok. These findings can serve as an evaluation material for Prolanis DM Type 2 patients to control their glycemic levels by routinely monitoring their HbA1c and triglyceride levels.